PENGARUH BEBERAPA PGPR (Plant Growth Promoting Rhizobacteria) TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) - adi Irfan; Mohammad Arief Aziz; Fitriah Suryani Jamin (Jurnal Lahan Pertanian Tropis (JLPT), 2022)
This study aims to determine which PGPR can increase the growth and production of cayenne pepper plants and to find out which type of PGPR has the most influence on the growth and production of cayenne pepper plants. This research was conducted in Tanggikiki Village, Sipatana District, Gorontalo City. The study started from April to July 2020. This study used a Randomized Block Design which consisted of 4 levels of treatment, namely PO = control, P1 = bamboo root, P2 = elephant grass root and P3 = Putri malu root. And 5 replications so that 20 experimental units/polybags were obtained. Each experimental unit contained 1 test plant, with a distance between polybags of 50 cm x 50 cm. The data from this study were analyzed using Analysis Of Variance (ANOVA) and then further tested with using BNT (Least Significant Difference) at the 5% level. The results showed that the PGPR treatment of the roots of the shy daughter gave the best results on plant height, number of leaves, number of fruits and fruit weight compared to treatment without PGPR.Keywords: PGPR, Bamboo roots, Elephant grass roots, Shy daughter roots, Cayenne pepper